"The Flesh of The Perceptible": The New Materialism of Leviathan. Issue 3 (October 2018) - Bowens, Max
Abstract : This article seeks to entangle two current philosophic praxes: New Materialism, and Sensory Ethnography. Jane Bennett has become one of New Materialism's most prominent proponents since the release of her now-seminal text, Vibrant Matter in 2010. Due to the varied ground upon which New Materialism stands (often conflated with object-oriented ontology, post-humanism, and other general turns within nonhumanism), Bennett's work will be looked at idiosyncratically, then pushed into the realm of the cinematic via an analysis of the documentary, Leviathan . Directed by Lucien Castaing-Taylor and Véréna Paravel, this film was among the first exemplary works to emerge from the Sensory Ethnography Lab, based at Harvard University. In striving for a revitalization of ethnographic film practices, the Lab aligns itself with similarly non-anthropocentric, and non-discursive, aspects of experience to the New Materialism of Jane Bennett. By placing these two contemporary camps into conversation, this article intends to reposition them both: New Materialism as a vehicle for the Sensory Ethnographic, and the SEL as an exhibition of the kind of world Bennett's philosophy envisages. The article concludes with an assessment of the political and eco-political critiques and ramifications surrounding these works.